Analysis of Issues Relating to Work Life Balance in Trucking Operation: A Human Resource Perspective - Singh, Akanksha; Parihar, Mahendra (International Journal of Computer Sciences and Engineering, 2025)
Today our world has become fast moving world. In the race of life we are losing a lot and gaining less with reference to overall growth from human perspective. Given this the work life balance has destructed like anything. However, in case of people with comparatively low level of income it has become worsen. Comparatively, the work life balance of people in organized sector is better than people in unorganized sector given no legislative and regulatory support in many ways. Having a look at various sectors and subsectors in our economy and specially unorganized sector in general and trucking sector in particular, the work life balance of its stake holders especially drivers, cleaners etc., is highly imbalance given the nature of the trucking industry and the way it functions in current context. As we are aware of the fact that the disturbance in work life balance affects the productivity of the stakeholders very negatively, the contribution of particular sector in economy with reference to output is less than the actual potential of particular sector. Moreover, trucking sector is one of the sector where the work life balance of its stakeholders, especially drivers and cleaners is highly imbalance due to the way trucking industry operates or functions currently despite the fact that it accounts for almost 65 percent of all the freight moved in the country along with having highest share in GDP from transportation sector. It is also said that a small inefficiency can translate into extensive national under-delivery and a small improvement can achieve the reverse, especially in case of trucking industry. Thus in this paper an attempt has been made to understand the nature of trucking industry in India with reference to nature of operations and try to analyze the situation relating to work life balance of drivers and cleaners. Also, an attempt is being made to analyze issue disturbing the work life work life balance and find out possible solutions in general and via regulation and legislative measures in particular